Fog and fogonomics challenges and practices of fog computing, communication, networking, strategy, and economics - Yang, Yang (John Wiley & Sons, Inc., 2020)
"Recent industry surveys expect the quantity of connected devices and sensors to be in excess of 50 billion worldwide by 2020, and these devices can generate huge amounts of data every single day. It becomes a big challenge to analyze and create actionable information from the data. Fog computing, as a promising solution to extend the capability of Clouds, has attracted considerable attention. Fogs are lightweight distributed technology platforms diffused among end-user devices in wired and wireless networks to provide highly scalable and resilient environments that can be utilized by organizations in a multitude of ways. Discusses pricing, service level agreements, service delivery, and consumption of fog computing Examines how fog will change the information and communication technology industry in the next decade . Describes how fog enables new business models, strategies, and competitive differentiation, as with ecosystems of connected, smart, digital products and services"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on March 30, 2020)
Keywords: Cloud computing; Infonuagique